2010
DOI: 10.18632/oncotarget.175
|View full text |Cite
|
Sign up to set email alerts
|

A molecular signature of normal breast epithelial and stromal cells from Li-Fraumeni syndrome mutation carriers

Abstract: AbstrAct:Specific changes in gene expression during cancer initiation should enable discovery of biomarkers for risk assessment, early detection and targets for chemoprevention. It has been previously demonstrated that altered mRNA and proteome signatures of morphologically normal cells bearing a single inherited "hit" in a tumor suppressor gene parallel many changes observed in the corresponding sporadic cancer. Here, we report on the global gene expression profile of morphologically normal, cultured primary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…An immortalized human mammary ASC line (HMS32-hTERT) was provided by Dr. Brittney-Shea Herbert (Indiana University School of Medicine) and grown as described previously (28,(41)(42)(43). Primary human breast ASCs and media were purchased from Zen-Bio.…”
Section: Cell Culturementioning
confidence: 99%
“…An immortalized human mammary ASC line (HMS32-hTERT) was provided by Dr. Brittney-Shea Herbert (Indiana University School of Medicine) and grown as described previously (28,(41)(42)(43). Primary human breast ASCs and media were purchased from Zen-Bio.…”
Section: Cell Culturementioning
confidence: 99%
“…First indications came from reports that Wnt signalling is activated in cells derived from Li–Fraumeni syndrome patients who carry germ‐line monoallelic TP53 mutations (Herbert et al . ; Okayama et al . ).…”
mentioning
confidence: 98%
“…There are several reports on the crosstalk of Wnt and p53 signalling pathways (Sadot et al 2001;Levina et al 2004;Kim et al 2011;Okayama et al 2014). First indications came from reports that Wnt signalling is activated in cells derived from Li-Fraumeni syndrome patients who carry germ-line monoallelic TP53 mutations (Herbert et al 2010;Okayama et al 2014). It has been shown that the excess p53 reduces beta-catenin protein levels and p53 can restrain Wnt signalling (Sadot et al 2001;Levina et al 2004;Kim et al 2011).…”
mentioning
confidence: 99%
“…Over the past 35 years, many genes have been identified which can cause or contribute to the formation of cancer. 27,28 These include two major classes of genes, the oncogenes [29][30][31][32][33] and the tumor-suppressor genes such as retinoblastoma (RB), [34][35][36][37] TP53, [38][39][40] BRCA1, 41,42 PTEN, 43 TSC1 and TSC2. [44][45][46][47] Many of these oncogenes and tumor suppressors are often critical regulators of cellular senescence.…”
Section: Ectopic Ngal Expression Can Alter Sensitivity Of Breast Cancmentioning
confidence: 99%